Zoomorphic code in the poetry of Kazimierz Święgocki - Zvonareva Л.У.; Chzhou Лу (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2018)
The authors of the article consider the work of the famous Polish poet of the middle generation, Doctor of Philosophy Kazimierz Svvegotsky on a wide cultural and historic-literary background. The stability of individual symbols and signs in the Eastern Slavic literature is traced by them from the era of Ivan the Terrible to the beginning of the 21-st century. The authors disclose hidden meanings and demonstrate the origins of images, to which the Polish poet has a special preference in his philosophical lyrics. Considering chronologically used images of animals, birds and insects in the artistic fabric of works, the authors note the following trends: with the years they become less and less. The poet was born in the countryside, studied and taught in the city, for many years the city life inevitably gradually alienated the living nature from the soul and heart of an impressionable creative person, which is immediately reflected in his work. The authors believe that in modern literature there is an active process that repeats the situation of the Silver Age: the active actualization of zoomorphic code in the texts of contemporary authors and in literary life.